Validation of the log e–log σ normal compression law using particle strength data - de Bono, John P.; McDowell, Glenn R. (Thomas Telford ICE Publishing, 2017)
This note is a study of experimental data on particle strength and normal compression, to establish whether the recently proposed normal compression law by McDowell and de Bono (2013) is supported and confirmed. A number of different sands are examined and found to support the hypothesis. In addition, some new simulations on sand mixtures are used to explain experimental results for quartz-feldspar mixtures. It would appear that the proposed compression law is also supported by the data for the sand mixtures.